Crecimiento urbano, ilegalidad y poderes locales en la ciudad de Puebla - Melé, Patrice (El Colegio de México A.C., 1989)
In this essay, the author attempts to delimit on a theoretical level, and given the situation of the City of Puebla, the space in which illegality is to be observed. He proposes to demonstrate that the distinction made between legal and illegal urban growth is not ap- propriate for Mexican urbanization. After reviewing theoretical concepts and advances made by different researchers who have dealt with the phenomenon of marginality and illegality, he considers the concrete situation of the City of Puebla, taking into account the manner in which the authorities have defined illegal urbanization and how the forms of production within the urban space have been occurring. The autor reaches the conclusion that it is better to define the dynamics of urbanization as an expression of different actors, rather than establishing a contrast between a legal and an illegal market. He also recommends that illegality is best studied on the basis of the social conditions under which it arises.